Transparent film and method for producing the same, laminate film and method for producing the same, and display device

By using semi-cured ultraviolet curing resin in the transparent film and adopting a specific manufacturing method, the problem of insufficient surface hardness of the transparent film in the prior art is solved, and a laminated film with high hardness and no easy breakage is achieved.

JP2025059445APending Publication Date: 2025-04-10DAI NIPPON PRINTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023169531
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

The prior art is difficult to increase the surface hardness of the transparent film without increasing the material brittleness to meet the protection needs of display equipment.

Method used

A semi-cured ultraviolet curing resin is used as the material of the transparent film, and the surface hardness of the transparent film is improved by a specific manufacturing method, including preparing a smooth substrate, forming an ultraviolet curing resin layer containing a meth acryloyl group, lamination and semi-curing treatment.

Benefits of technology

It is achieved that the transparent film has a significant increase in surface hardness while maintaining the non-brittleness characteristics, so that the laminated film formed has the characteristics of high hardness and is not easy to break.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059445000001_ABST
    Figure 2025059445000001_ABST
Patent Text Reader

Abstract

To provide an optical transparent film which enables production of a laminate film that is difficult to be broken while having high surface hardness.SOLUTION: A transparent film containing a semi-cured ultraviolet curable resin can be formed into a laminate having less warpage by laminating an uncured product of a functional layer such as a hard coat layer and simultaneously curing the uncured product, and enables production of a laminate film having high surface hardness and no warpage. Brightness maximum point density calculated from an observation image by a scanning type electronic microscope of a cross section in a thickness direction of the transparent film is 20 pieces / μm2 or more and 200 pieces / μm2 or less.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a transparent film and a method for producing the same, a laminated film and a method for producing the same, and a display device. [Background technology]

[0002] Conventionally, a cover member made of glass or resin is used in a display device to protect the display device. This cover member protects the display device from impact and scratches, and is required to have impact resistance, scratch resistance, and the like. A glass cover member has characteristics such as high surface hardness, scratch resistance, and high transparency. On the other hand, a glass cover member is heavy, very rigid, difficult to bend, and easily breakable. For this reason, in recent years, resin cover members are replacing glass products in terms of workability and weight reduction, and research has been conducted on resin products that can replace glass.

[0003] Resin cover members have a lower surface hardness than glass cover members, and techniques for increasing the surface hardness have been proposed. For example, a laminated film in which a hard coat layer is laminated on a resin substrate has been proposed. However, resin substrates such as PET and TAC have a low hardness of the resin substrate itself, so that sufficient surface hardness cannot be obtained even if a hard coat layer is laminated. In addition, resin substrates formed from ultraviolet-curable resin compositions tend to warp significantly. Therefore, the hard coat layer cannot be applied thickly, and it is difficult to obtain sufficient surface hardness.

[0004] As a technique for increasing surface hardness, Patent Document 1 discloses a cover film having a transparent substrate layer and a transparent surface layer, in which the substrate layer contains a predetermined amount of a urethane-based (meth)acrylate and a di- or higher functional (meth)acrylate, the surface layer contains a predetermined amount of a tetra- or higher functional (meth)acrylate, and the substrate layer and the surface layer each have a predetermined thickness.

[0005] Patent Document 2 discloses a surface protection film including a transparent film formed of an ultraviolet-curable acrylic resin containing a multifunctional urethane (meth)acrylate and a multifunctional (meth)acrylate, and a hard coat layer formed of an ultraviolet-curable resin, in which the surface of the hard coat layer of the surface protection film has a pencil hardness of 8H or more, a predetermined number of times or more of scratches have been confirmed in a steel wool sliding test, and an initial pure water contact angle is a predetermined value or more. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6844057 [Patent Document 2] Patent No. 6677537 Summary of the Invention [Problem to be solved by the invention]

[0007] A cover film (laminate film) including a transparent film made of an ultraviolet-curable resin composition containing a urethane-based (meth)acrylate as a substrate, as described in Patent Documents 1 and 2, has high surface hardness, but is hard and brittle and easily breaks.

[0008] The present disclosure has been made in consideration of the above circumstances, and has as its main object to provide a transparent film that can provide a laminated film that has high surface hardness and is difficult to break. [Means for solving the problem]

[0009] One embodiment of the present disclosure is an optical transparent film, the transparent film comprising a semi-cured ultraviolet curable resin, and a luminance maximum point density calculated from an image of a cross section of the transparent film in a thickness direction observed by a scanning electron microscope is 20 pieces / μm 2 More than 200 pieces / μm 2 Below is a transparent film.

[0010] One embodiment of the present disclosure is a method for producing the above-mentioned transparent film, comprising: a preparation step of preparing two substrate films having smooth surfaces; a coating layer A formation step of applying an ultraviolet-curable resin composition A having a polymerizable polymer having a skeleton represented by the following general formula (2) and a multifunctional (meth)acrylate monomer having three or more (meth)acryloyl groups in the molecule onto the smooth surface of one of the substrate films to form a coating layer A; a lamination step of laminating the other substrate film so that the smooth surface is in contact with the coating layer A to form a laminate film; and a semi-curing step of irradiating the laminate film with ultraviolet light to semi-cure the coating layer A and obtain the transparent film from the coating layer A.

[0011] [ka] (In the formula, X represents a divalent organic group, and R 1 and R 2 each independently represents a (meth)acryloyl group-containing group, and n represents the average degree of polymerization and is a number from 50 to 130.

[0012] One embodiment of the present disclosure includes a cured film including an ultraviolet curable resin and a functional layer disposed on one surface of the cured film, the brightness maximum point density calculated from an image of a cross section of the cured film in a thickness direction observed by a scanning electron microscope being 20 pieces / μm 2 More than 200 pieces / μm 2 The laminated film is shown below.

[0013] One embodiment of the present disclosure is a method for producing a laminate film, comprising: a coating layer B formation step of applying an ultraviolet-curable resin composition B for a functional layer to one side of the above-mentioned transparent film to form a coating layer B, thereby obtaining a laminate having the above-mentioned transparent film and the above-mentioned coating layer B; and an integral curing step of irradiating the above-mentioned laminate with ultraviolet light to cure the above-mentioned transparent film and the above-mentioned coating layer B as a whole, thereby obtaining a cured film from the above-mentioned transparent film and obtaining the above-mentioned functional layer from the above-mentioned coating layer B.

[0014] One embodiment of the present disclosure is a display device including a display panel and the above-mentioned laminate film disposed on a viewer's side of the display panel. Effect of the Invention

[0015] According to the present disclosure, it is possible to provide a transparent film that can produce a laminated film that has high surface hardness and is resistant to breakage. [Brief description of the drawings]

[0016] [Figure 1] 1 is a schematic cross-sectional view illustrating a transparent film of the present disclosure. [Diagram 2] 1 is a cross-sectional flow diagram illustrating a method for producing a transparent film according to the present disclosure. [Diagram 3] FIG. 2 is a schematic diagram illustrating a method for producing a transparent film according to the present disclosure using a roll-to-roll process. [Figure 4] 1 is a schematic cross-sectional view illustrating a laminated film according to the present disclosure. [Diagram 5] FIG. 2 is an analytical image and an enlarged view showing maximum brightness points obtained by analyzing an SEM observation image of a cross section of the transparent film of Example 1. [Figure 6] FIG. 13 is an analytical image and an enlarged view showing maximum brightness points obtained by analyzing an SEM observation image of a cross section of the transparent film of Example 3. [Figure 7] FIG. 2 is an analytical image and an enlarged view showing maximum brightness points obtained by analyzing an SEM observation image of a cross section of the transparent film of Comparative Example 1. [Figure 8]FIG. 2 is an analytical image and an enlarged view showing maximum brightness points obtained by analyzing an SEM observation image of a cross section of the transparent film of Comparative Example 2. [Figure 9] 1 is a schematic cross-sectional view illustrating a display device according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The following describes the embodiments of the present disclosure with reference to the drawings. However, the present disclosure can be implemented in many different forms, and should not be interpreted as being limited to the description of the embodiments exemplified below. In addition, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the actual form in order to make the explanation clearer, but these are merely examples and do not limit the interpretation of the present disclosure. In this specification and each figure, elements similar to those described above with respect to the previous figures may be given the same reference numerals, and detailed explanations may be omitted as appropriate.

[0018] In this specification, when describing a mode in which another component is disposed on a certain component, the term "above" or "below" is used, unless otherwise specified, to include both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween. Also, in this specification, when describing a mode in which another component is disposed on the surface of a certain component, the term "on the surface side" or "on the surface" is used, unless otherwise specified, to include both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween.

[0019] The transparent film and its manufacturing method, the laminate film and its manufacturing method, and the display device according to the present disclosure will be described in detail below.

[0020] A. Transparent film The transparent film of the present disclosure is used for optical purposes. Fig. 1 is a schematic cross-sectional view showing an example of the transparent film of the present disclosure. As shown in Fig. 1, the transparent film 1 of the present disclosure contains an ultraviolet curable resin, and has a thickness direction D of the transparent film 1. T The density of maximum brightness points calculated from the cross-sectional image observed by a scanning electron microscope (SEM) is 20 points / μm 2 More than 200 pieces / μm 2 The following is the result.

[0021] According to the present disclosure, the thickness direction D T Since the density of maximum brightness points calculated from a cross-sectional image observed by a scanning electron microscope is within a predetermined range, the transparent film has high hardness and suppressed brittleness. By using such a transparent film as a substrate, a laminate film having high surface hardness and being difficult to break can be obtained.

[0022] FIG. 5(a) shows the thickness direction D of the transparent film of the present disclosure (the transparent film of Example 1). T Fig. 5(b) is an analysis image showing the brightness maximum points, which was obtained by image processing the SEM observation image of the cross section in Fig. 5(a). Fig. 5(b) is an enlarged view of the square frame in Fig. 5(a), and the brightness maximum points are indicated by M. A large number of brightness maximum points M means that there are many irregularities formed on the cross section.

[0023] Here, it is assumed that the numerous projections and recesses are particulate aggregates formed by the aggregation of hard segments contained in the ultraviolet curable resin in the transparent film. 2 It can be said that the number of particulate aggregates per 1000 nm is the number of particulate aggregates per 1000 nm. In the case of the transparent film of the present disclosure, since the luminance maximum point density is equal to or greater than the above value, a large number of particulate aggregates are present, which is presumed to improve the hardness of the transparent film of the present disclosure. Furthermore, since the particulate aggregates are also bonded together by a polymerizable compound (e.g., a relatively large polymerizable polymer), it is presumed that the transparent film has improved brittleness.

[0024] In addition, the brightness maximum point is presumed to be derived from particulate aggregates as described above, and is not derived from fine particles. If it is derived from fine particles, the transparent film may become brittle. Therefore, the transparent film of the present disclosure preferably contains 20% by mass or less of fine particles, particularly preferably 10% by mass or less, and more preferably does not contain fine particles.

[0025] 1. Brightness maximum point density The transparent film of the present disclosure has a thickness direction D T The density of maximum brightness points calculated from the cross-sectional image observed by a scanning electron microscope (SEM) is 20 / μm 2 More than 40 pieces / μm 2 More preferably, 60 particles / μm 2 If the luminance maximum density is equal to or greater than the above value, the hardness of the transparent film is improved and the brittleness is suppressed. 2 Less than 190 particles / μm 2 It is preferable that the number of particles is less than 180 / μm. 2 If the brightness maximum point density is greater than the above value, it is presumed that the hard segments will not be bonded together, and brittleness cannot be suppressed.

[0026] In the present disclosure, the luminance maximum point density is a value obtained by the following measurement method. First, the transparent film is T Specifically, the transparent film is folded in half at 180° and cut to expose the cross section in the thickness direction. The brightness maximum point density is measured using a scanning electron microscope (SEM) and image processing software. Specifically, an image of the cross section of a transparent film taken at 30,000 times magnification using a scanning electron microscope (SEM) is read into image processing software (product name "ImageJ", manufactured by the National Institutes of Health, USA), and image processing is performed. In detail, the following steps (1) to (4) are performed.

[0027] (1) Confirm that the pixel count of the captured image (4.17 μm × 3.14 μm area) is 1280 × 960 pixels (calculated as 307 pixels = 1.00 μm) and 8 bits. (2) Apply a noise removal filter to the image by selecting "Process", "Filters", "Median", and "Radius 1.0 pixels", and then select "Process", "Filters", "Top Hat", and "Radius 1.0 pixels" to extract convex structures in the image. (3) Select "Process", "Find Maxima", "Prominence 20.00", "Output type List", and "Preview point section" to detect the position of the convex structure (brightness maximum point) in the image. Then, output a CSV file from "Output type List". (4) The brightness maximum point density is determined by dividing the image into 100 regions of 128 pixels x 96 pixels, and the arithmetic mean value of the densities calculated for each divided region is used as the brightness maximum point density.

[0028] The luminance maximum point density can be adjusted by the composition of the ultraviolet curable resin composition, for example, the type and amount of polymerizable polymer, polymerizable monomer, etc. For example, by increasing the amount of polymerizable polymer, the luminance maximum point density tends to increase. In addition, among polymerizable polymers, those with a larger molecular weight tend to have a higher luminance maximum point density. For example, by using a polymerizable polymer with a molecular weight of 15,000 or more, preferably a polymerizable polymer with a molecular weight of 24,000 or more, the luminance maximum point density tends to increase. In addition, by increasing the number of terminal functional groups (e.g., (meth)acryloyl groups) in the polymerizable polymer, the luminance maximum point density tends to increase.

[0029] 2.UV curable resin The transparent film of the present disclosure includes a semi-cured ultraviolet-curable resin. The semi-cured state means that the resin can be further cured by a subsequent curing process. Specifically, the semi-cured state means that the ultraviolet-curable resin has unreacted functional groups that contribute to curing by ultraviolet light.

[0030] The ultraviolet curable resin in the present disclosure is in a semi-cured state, and can be fully cured by further curing. A transparent film containing a semi-cured ultraviolet curable resin can be made into a laminate with little warping by laminating an uncured material of a functional layer such as a hard coat layer and curing it at the same time, and a laminate film with high surface hardness and no warping can be obtained.

[0031] The proportion of the mass of the ultraviolet curable resin to the total mass of the transparent film of the present disclosure is, for example, 90% or more, may be 95% or more, or may be 100%.

[0032] The crosslinking rate of the transparent film of the present disclosure (i.e., the crosslinking rate of the ultraviolet curable resin) is, for example, 20% or more, may be 30% or more, or may be 40% or more, while it is, for example, 90% or less, may be 80% or less, or may be 70% or less.

[0033] The crosslinking rate of the transparent film is a value calculated as follows. The absorption spectra of the uncured ultraviolet-curable resin composition and the transparent film are obtained by IR measurement (infrared spectroscopy measurement), and the peak intensities (absorbances) P0 and P1 of the peaks derived from the ultraviolet-curable functional group in each absorption spectrum are obtained, and the crosslinking rate is calculated according to the following formula. For example, the peak derived from the (meth)acryloyl group, which is the ultraviolet-curable functional group, has an intensity of 810 cm -1 appears nearby. Crosslinking rate (%) = (1 - (peak strength P1 of transparent film / peak strength P0 of uncured ultraviolet-curable resin composition)) x 100 (%) The uncured ultraviolet-curable resin composition is a composition containing a resin in which unreacted functional groups that contribute to curing by ultraviolet light are present and have not yet reacted. Specifically, the uncured ultraviolet-curable resin composition A can be determined by measuring the ultraviolet-curable resin composition A.

[0034] In the present disclosure, it is preferable that a pyrolyzate obtained by pyrolyzing a transparent film has a skeleton represented by the following general formula (1).

[0035] [ka] (In the formula, X represents a divalent organic group.)

[0036] X represents a divalent organic group. The divalent organic group of X is, for example, a hydrocarbon group having 1 to 15 carbon atoms, and among them, an aliphatic hydrocarbon group, an aromatic hydrocarbon group, an alicyclic hydrocarbon group, etc. can be mentioned. These hydrocarbon groups may be linear, branched, or cyclic, or may be a combination of linear or branched and cyclic. X is, for example, an alkylene group, an alkenylene group, an arylene group, or a combination thereof. The alkylene group and the alkenylene group can be linear, branched, or cyclic, or may be a combination of linear or branched and cyclic. Specific examples include methylene, ethylene, vinylene, propenylene, propylene, cyclopropylene, butylene, cyclobutylene, cyclohexylene, norbornylene, isobornylene, dicyclopentanylene, adamantylene, and a combination of a linear or branched alkylene group and a cyclic alkylene group, such as a methylenecyclohexylenemethylene group. Among these, alicyclic hydrocarbon groups such as a 1,1-cyclohexylene group are preferred.

[0037] It can be confirmed that the pyrolysate has the skeleton of the above general formula (1) by pyrolysis gas chromatography mass spectrometry using a simultaneous pyrolysis and derivatization method. Specifically, a sample taken from a transparent film is analyzed by pyrolysis gas chromatography mass spectrometry using the following procedure and measurement conditions. A standard sample (a polymerizable polymer having the skeleton of the above general formula (1), for example, polymerizable polymer 1 in the examples) is also measured under the same conditions. By comparing the total ion chromatogram with the mass spectrum of each peak, it is possible to confirm that the pyrolysis product has the skeleton of the above general formula (1) by observing a specific mass fragment peak derived from the polymerizable polymer from the transparent film at the same retention time.

[0038] <Pyrolysis GCMS> (Procedure and measurement conditions) (1) Dry the sample using a dryer, oven, etc. (2) Place approximately 0.1 mg of sample into the sample cup. (3) Add approximately 1 μL of TMAH to the sample cup. (4) Place the sample cup in the pyrolysis apparatus and perform the measurement. Measurement equipment (Agilent Technologies) ○ Pyrolysis equipment (Frontier Labs) ○Column (Frontier Labs) ○GC-MS measurement conditions Injection temperature: 320℃ Carrier gas: Helium 1.7ml / min constant flow mode ○ Pyrolysis furnace measurement conditions ·Thermal decomposition temperature: 600℃

[0039] As described above, the ultraviolet curable resin is a semi-cured product of an ultraviolet curable resin composition. The ultraviolet-curable resin composition used in the present disclosure (hereinafter, in the present disclosure, may be referred to as ultraviolet-curable composition A) will be described below.

[0040] The ultraviolet-curable resin composition A used in the present disclosure is a composition containing a compound having an ultraviolet-curable functional group (hereinafter, also referred to as an "ultraviolet-curable compound"). The ultraviolet-curable functional group is a group that crosslinks and cures when irradiated with ultraviolet light. Preferred examples of the ultraviolet-curable functional group include functional groups having an ethylenic double bond, such as a (meth)acryloyl group, a vinyl group, and an allyl group.

[0041] The term "(meth)acryloyl group" refers to an acryloyl group or a methacryloyl group, and the term "(meth)acrylate" refers to an acrylate or a methacrylate.

[0042] The ultraviolet-curable resin composition A preferably has a polymerizable polymer having a skeleton represented by the following general formula (2) as an ultraviolet-curable compound. It is assumed that the inclusion of such a polymerizable polymer makes it easier to form an aggregate of hard segments by crosslinking with other polymerizable monomers. This makes it easier to form particles observed as luminance maximum points, and makes it easier to fall within the above-mentioned range of luminance maximum point density. This tends to improve brittleness while maintaining hardness.

[0043] [ka] (In the formula, X represents a divalent organic group, and R 1 and R 2 each independently represents a (meth)acryloyl group-containing group, and n represents the average degree of polymerization and is a number from 50 to 130.

[0044] R 1 and R 2 each independently represents a (meth)acryloyl group-containing group. Examples include -OC(=O)CH=CH2, -OC(=O)C(CH3)=CH2, -C(CH3)2CH2OC(=O)CH=CH2, -C(CH3)2CH2OC(=O)C(CH3)=CH2, and the like. n represents the average degree of polymerization and is a number from 50 to 130, and may be a number from 80 to 100.

[0045] The weight average molecular weight of the polymerizable polymer having the skeleton represented by the above general formula (2) is, for example, 20,000 or more and 40,000 or less, and preferably 25,000 or more and 30,000 or less. When the weight average molecular weight is within the above range, the above luminance maximum point density is easily obtained.

[0046] The proportion of the polymerizable polymer having a skeleton represented by the above general formula (2) relative to the total mass of the ultraviolet curable compounds contained in the ultraviolet curable resin composition A is, for example, 5 mass% or more, or may be 10 mass% or more, or may be 15 mass% or more, while it is, for example, 40 mass% or less, or may be 30 mass% or less.

[0047] The ultraviolet curable resin composition A may contain a polymerizable monomer as an ultraviolet curable compound. As the polymerizable monomer, a (meth)acrylate monomer is preferable, and among them, a polyfunctional (meth)acrylate monomer having three or more (meth)acryloyl groups in the molecule is preferable. By using such a polyfunctional (meth)acrylate monomer having three or more (meth)acryloyl groups together with the polymerizable polymer, the above-mentioned luminance maximum point density is easily obtained. This tends to improve the surface hardness.

[0048] As such a polyfunctional (meth)acrylate monomer, for example, pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA), pentaerythritol tetraacrylate (PETTA), dipentaerythritol pentaacrylate (DPPA), trimethylolpropane tri(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, etc. can be preferably used. In particular, at least one selected from pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexaacrylate is preferable.

[0049] The proportion of the polyfunctional (meth)acrylate monomer to the total mass of the ultraviolet curable compounds contained in the ultraviolet curable resin composition A is, for example, 20% by mass or more, or may be 30% by mass or more, or may be 40% by mass or more, while it is, for example, 60% by mass or less, or may be 50% by mass or less.

[0050] In order to improve the coating property of the ultraviolet-curable resin composition A, the polymerizable monomer may contain a bifunctional (meth)acrylate monomer having two (meth)acryloyl groups in the molecule. Such a bifunctional (meth)acrylate monomer preferably has an alicyclic hydrocarbon structure. The alicyclic hydrocarbon structure may be at least one selected from a tetrahydrodicyclopentadiene ring and a dihydrodicyclopentadiene ring.

[0051] The proportion of the bifunctional (meth)acrylate monomer to the total mass of the ultraviolet curable compounds contained in the ultraviolet curable resin composition A is, for example, 5% by mass or more, and may be 10% by mass or more, while it is, for example, 30% by mass or less, and may be 20% by mass or less.

[0052] From the viewpoint of improving the coatability of the ultraviolet curable resin composition A, the ultraviolet curable compound preferably contains a cyclopolymerizable monomer. In the present disclosure, the cyclopolymerizable monomer refers to a polymerizable monomer that can undergo a cyclization reaction within the molecule during polymerization. The cyclopolymerizable monomer is preferably an α-allyloxymethyl acrylic acid ester.

[0053] Examples of α-allyloxymethyl acrylic acid esters include methyl α-allyloxymethylacrylate, ethyl α-allyloxymethylacrylate, n-propyl α-allyloxymethylacrylate, i-propyl α-allyloxymethylacrylate, n-butyl α-allyloxymethylacrylate, s-butyl α-allyloxymethylacrylate, t-butyl α-allyloxymethylacrylate, n-hexyl α-allyloxymethylacrylate, and 2-ethylhexyl α-allyloxymethylacrylate.

[0054] The ratio of the cyclopolymerizable monomer to the total mass of the ultraviolet curable compounds contained in the ultraviolet curable resin composition A is, for example, 20% by mass or more, and may be 30% by mass or more, while it is, for example, 50% by mass or less, and may be 40% by mass or less.

[0055] The ultraviolet curable resin composition A preferably contains at least one of a photopolymerization initiator and a photopolymerization accelerator. Examples of the photopolymerization initiator include acetophenone, benzophenone, α-hydroxyalkylphenone, Michler's ketone, benzoin, benzyl dimethyl ketal, benzoyl benzoate, α-acyloxime ester, acylphosphine oxide, and thioxanthones. Examples of the photopolymerization accelerator include p-dimethylaminobenzoic acid isoamyl ester and p-dimethylaminobenzoic acid ethyl ester.

[0056] The ultraviolet curable resin composition A preferably does not substantially contain a solvent. Here, "substantially does not contain a solvent" means that it does not contain any solvent other than the solvent unintentionally contained, such as impurities. That is, for example, the content of the solvent in the ultraviolet curable resin composition of the present disclosure is preferably 1% by weight or less, more preferably 0.5% by weight or less, based on the entire ultraviolet curable resin composition.

[0057] 3.Transparent film The transparent film has a thickness of, for example, 80 μm or more and 500 μm or less, preferably 100 μm or more and 400 μm or less.

[0058] The transparent film of the present disclosure can be used for optical applications by forming it into a cured film as described below. For example, it can be used as a substrate for a functional film (a laminated film having a functional layer) in a display device, more specifically, as a substrate for a functional film used as a front panel, that is, a member disposed on the observer side of a display panel in a display device.

[0059] B. Transparent Film Manufacturing Method Fig. 2 is a cross-sectional flow diagram illustrating a method for producing a transparent film in the present disclosure. As shown in Fig. 2, the method for producing a transparent film in the present disclosure is the above-mentioned method for producing a transparent film, and includes a preparation step of preparing two base films 20A and 20B having smooth surfaces, a coating layer A formation step (Fig. 2(a)) of coating the above-mentioned ultraviolet-curable resin composition A having a polymerizable polymer having a skeleton represented by the following general formula (2) and a polyfunctional acrylic monomer having three or more (meth)acryloyl groups in the molecule on the smooth surface of one of the base films 20A to form a coating layer A21, a lamination step (Fig. 2(b)) of laminating the other base film 20B so that the smooth surface is in contact with the coating layer A21 to form a laminate film 22, and a semi-curing step (Fig. 2(c), Fig. 2(d)) of irradiating the laminate film 22 with ultraviolet light to semi-cure the coating layer A21 to obtain the transparent film 1 from the coating layer A21.

[0060] [ka] (In the formula, X represents a divalent organic group, and R 1 and R 2 each independently represents a (meth)acryloyl group-containing group, and n represents the average degree of polymerization and is a number from 50 to 130.

[0061] According to the transparent film manufacturing method of the present disclosure, a transparent film can be manufactured that can be made into a laminated film with little warping and high hardness by disposing a functional film, such as a hard coat film, in an uncured state on the obtained transparent film and curing them at the same time.

[0062] 1. Preparation process In this step, two substrate films having smooth surfaces are prepared. The substrate film is not particularly limited as long as it is a transparent film, and may be formed from, for example, polyethylene terephthalate, polyamide, polycarbonate, acrylic resin, polyolefin resin such as polypropylene and polyethylene, cellulose resin such as diacetyl cellulose and cetyl cellulose, polyvinylidene chloride, etc. In order to facilitate peeling from the transparent film in the peeling step described below, a release layer containing a fluorine-based additive or the like may be formed on one surface of the base film.

[0063] 2. Coating layer A formation process In this step, the above-mentioned ultraviolet-curable resin composition A is applied onto the smooth surface of one of the base films to form a coating layer A. The ultraviolet-curable resin composition A applied in this step is as described above, and therefore a description thereof will be omitted here.

[0064] Examples of the method for applying the ultraviolet-curable resin composition A include gravure printing, bar coating, roll coating, reverse roll coating, and comma coating.

[0065] In coating the ultraviolet-curable resin composition A, it is preferable to coat the composition so that the thickness after semi-curing (thickness when made into a transparent film) is, for example, 80 μm or more and 500 μm or less, preferably 100 μm or more and 400 μm or less.

[0066] 3.Lamination process This step is a step of forming a laminate film by laminating the other base film so that the smooth surface is in contact with the coating layer A. The laminate film has at least the base film, the coating layer A and the base film in this order.

[0067] 4. Semi-curing process In this step, the laminate film is irradiated with ultraviolet light to semi-cure the coating layer A, and a transparent film is obtained from the coating layer A. It is preferable that the coating layer A is cured (semi-cured) so that the crosslinking rate is 20% or more and 90% or less. The ultraviolet light irradiation may be performed from the base film 20A side of the laminate film, from the base film 20B side, or from both sides. In FIG. 2(c), ultraviolet light is irradiated from both the base film 20A side and the base film 20B side of the laminate film.

[0068] As a light source for irradiating ultraviolet rays, light sources such as ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arc lamps, black light fluorescent lamps, metal halide lamps, ultraviolet LEDs, etc. can be used. The wavelength of ultraviolet rays is about 190 to 380 nm. The irradiation amount (integral light amount) of ultraviolet rays is preferably an irradiation amount that can cure the coating layer so that the crosslinking rate is 20% or more and 90% or less. For example, 100 mJ / cm 2 ~1500mJ / cm 2 and preferably in the range of 100 mJ / cm 2 ~800mJ / cm 2 It is more preferable that the range is within the range.

[0069] 5. Other processes The method for producing a transparent film according to the present disclosure preferably includes, after the curing step, a peeling step of peeling the two base films from the laminate film to obtain a single transparent film.

[0070] 6.Other In the manufacturing method of the transparent film of the present disclosure, the above-mentioned preparation fixing, coating layer A forming step, lamination step, and semi-curing step may be performed continuously. Specifically, it is preferable to perform them continuously by a roll-to-roll method. FIG. 3 is a schematic diagram illustrating the manufacturing method of the transparent film of the present disclosure using the roll-to-roll method. In FIG. 3, the above-mentioned ultraviolet curable resin composition A32 is applied to the base film 20A unwound from the winding roll by a comma coater 31 to form the coating layer A21, and the other base film 20B unwound from the winding roll is laminated on the coating layer A21 to form the laminate film 22, which is irradiated with ultraviolet light and then cooled by a cooling roll Rc, and the coating layer A21 is made into the transparent film 1, which is then wound into a roll.

[0071] C. Laminated film The laminate film of the present disclosure includes a cured film containing an ultraviolet curable resin and a functional layer disposed on one surface of the cured film, and the cured film has a maximum brightness point density of 20 points / μm as calculated from an image of a cross section of the cured film in a thickness direction observed by a scanning electron microscope. 2 More than 200 pieces / μm 2 It is as follows:

[0072] 4 is a schematic cross-sectional view illustrating a laminated film according to the present disclosure. As shown in FIG. 4, a laminated film 10 according to the present disclosure includes a cured film 11 and a functional layer 2 disposed on one surface of the cured film 11.

[0073] The laminate film of the present disclosure has a brightness maximum point density of 20 / μm as calculated from a cross-section image in the thickness direction observed by a scanning electron microscope. 2 More than 200 pieces / μm 2 Since the cured film has a hardness of 0.1 to 100%, the laminate film has high surface hardness and reduced brittleness.

[0074] In addition, the laminated film of the present disclosure can be produced, for example, by integrally curing the transparent film and the UV-curable resin composition for the functional layer. Therefore, curing shrinkage occurs in both the transparent film and the UV-curable resin composition for the functional layer, resulting in a laminated film with suppressed warping. Furthermore, the unreacted functional group of the transparent film reacts with the functional group contained in the UV-curable resin composition for the functional layer, resulting in a laminated film with high adhesion strength between the transparent film and the functional layer.

[0075] The functional layer may be a single layer or may have multiple layers. The functional layer may be a layer having a single function or may have multiple layers having different functions. In the present disclosure, the functional layer preferably has a hard coat layer. As described above, since the hardness of the transparent film is high, it is possible to increase the surface hardness by a synergistic effect with the hard coat layer. Therefore, by disposing the hard coat layer, the scratch resistance can be further improved.

[0076] (1) Cured film The maximum brightness point density in the cured film in this disclosure is the same as that described in the above section "A. Transparent film", so the description here is omitted. In addition, the ultraviolet curing resin contained in the cured film is a cured product of the ultraviolet curing resin described in the above section "A. Transparent film".

[0077] Therefore, like the transparent film, the cured film preferably has a pyrolysis product obtained by pyrolyzing the cured film, which has the skeleton of the above-mentioned general formula (1). Similarly to the thickness of the transparent film, the thickness of the cured film is, for example, 80 μm or more and 500 μm or less, and preferably 100 μm or more and 400 μm or less.

[0078] The cured film in the present disclosure can be obtained by curing the transparent film described above in the section "A. Transparent film." Therefore, the crosslinking rate of the cured film is not particularly limited as long as it is higher than the crosslinking rate of the transparent film. The crosslinking rate of the cured film is, for example, 50% or more, preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more, and may be more than 90%. By setting it in the above range, high hardness can be obtained.

[0079] (2) Functional layer (2-1) Hard coat layer The functional layer preferably includes a hard coat layer. When the functional layer has a hard coat layer, the hard coat layer and the above-mentioned cured film are preferably in direct contact with each other. On the other hand, the hard coat layer and the above-mentioned cured film do not necessarily have to be in direct contact with each other.

[0080] (a) Material for hard coat layer The material of the hard coat layer is preferably an organic material. Specifically, the hard coat layer preferably includes a cured product of a resin composition containing an ultraviolet curable compound. The cured product of the resin composition containing an ultraviolet curable compound can be obtained by polymerizing the ultraviolet curable compound by a known method using a polymerization initiator as necessary.

[0081] (i) Ultraviolet curable compound The ultraviolet-curable compound used as the material for the hard coat layer has at least one polymerizable functional group in the molecule, and is preferably, for example, a polyfunctional (meth)acrylate.

[0082] Examples of polyfunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, di Trimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, isocyanuric acid tri(meth)acrylate, isocyanuric acid di(meth)acrylate, polyester tri(meth)acrylate, polyester di(meth)acrylate, bisphenol di(meth)acrylate, diglycerin tetra(meth)acrylate, adamantyl di(meth)acrylate, isobornyl di(meth)acrylate, dicyclopentaerythritol Examples of such acrylates include benzene di(meth)acrylate, tricyclodecane di(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and those modified with PO, EO, caprolactone, etc. Among these, from the viewpoint of improving surface hardness, those having three to six functional groups are preferred, and for example, pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA), pentaerythritol tetraacrylate (PETTA), dipentaerythritol pentaacrylate (DPPA), trimethylolpropane tri(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, etc. are preferred.

[0083] (ii) Polymerization initiator The resin composition may contain a polymerization initiator as necessary. Examples of the polymerization initiator include the same polymerization initiators as those in the ultraviolet-curable resin composition for the transparent film described above.

[0084] (iii) particles The hard coat layer preferably contains inorganic particles or organic particles, and more preferably contains inorganic fine particles. When the hard coat layer contains particles, the hardness can be improved.

[0085] Examples of inorganic particles include metal oxide particles such as silica (SiO2), aluminum oxide, zirconia, titania, zinc oxide, germanium oxide, indium oxide, tin oxide, indium tin oxide (ITO), antimony oxide, and cerium oxide, metal fluoride particles such as magnesium fluoride and sodium fluoride, metal particles, metal sulfide particles, and metal nitride particles. Among these, metal oxide particles are preferred, and at least one selected from silica particles and aluminum oxide particles is more preferred, with silica particles being even more preferred. This is because excellent hardness can be obtained.

[0086] Among the silica particles, reactive silica particles are preferred. The reactive silica particles are silica particles that can form a crosslinked structure with the polyfunctional (meth)acrylate, and the hardness of the hard coat layer can be sufficiently increased by including the reactive silica particles.

[0087] The reactive silica particles preferably have a reactive functional group on the surface thereof, and as the reactive functional group, for example, the above-mentioned polymerizable functional group is preferably used. The reactive silica particles are not particularly limited, and conventionally known ones can be used, for example, reactive silica particles described in JP-A-2008-165040, etc. In addition, commercially available reactive silica particles include MIBK-SD, MIBK-SDMS, MIBK-SDL, MIBK-SDZL manufactured by Nissan Chemical Industries, Ltd., and V8802, V8803, etc. manufactured by JGC Catalysts and Chemicals Co., Ltd.

[0088] The silica particles may be spherical silica particles, but are preferably irregular silica particles. In this specification, the term "spherical silica particles" refers to silica particles such as spherical or elliptical silica particles, and the term "irregular silica particles" refers to silica particles having random potato-shaped irregularities on the surface. The irregular silica particles have a larger surface area than spherical silica particles, so that the contact area with the polyfunctional (meth)acrylate, etc. is increased by including such irregular silica particles, and the hardness of the hard coat layer can be improved. The irregular silica particles can be confirmed by observing the cross section of the functional layer using a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM).

[0089] The average particle diameter of the silica particles is preferably 8 nm or more and 100 nm or less. When the silica particles are spherical silica particles, the average particle diameter of the silica particles is a value measured using image processing software from an image taken by a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM). When the silica particles are irregular silica particles, the average particle diameter of the silica particles is the average value of the maximum (long axis) and minimum (short axis) of the distance between two points on the periphery of the irregular silica particles that appear in an image taken by a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM).

[0090] The hardness of the hard coat layer can be controlled by adjusting the size and content of the inorganic particles. For example, the content of the silica particles is preferably 50 parts by mass or more and 100 parts by mass or less, more preferably 60 parts by mass or more and 80 parts by mass or less, based on 100 parts by mass of the ultraviolet curable compound.

[0091] (iv) Antifouling agents The hard coat layer may contain an antifouling agent, which can impart antifouling properties to the laminated film.

[0092] The antifouling agent is not particularly limited, and examples thereof include silicone-based antifouling agents, fluorine-based antifouling agents, and silicone-based and fluorine-based antifouling agents. The antifouling agent may also be an acrylic-based antifouling agent. The antifouling agent may be used alone or in combination of two or more.

[0093] The hard coat layer containing the silicone-based antifouling agent or the fluorine-based antifouling agent is less susceptible to fingerprints (less noticeable) and has good wiping properties. In addition, when the silicone-based antifouling agent or the fluorine-based antifouling agent is contained, the surface tension during application of the hard coat layer curable resin composition can be reduced, resulting in good leveling properties and a good appearance of the obtained hard coat layer.

[0094] In addition, the hard coat layer containing the silicone-based antifouling agent has good slipperiness and good scratch resistance. In a display device including a laminate film having a hard coat layer containing such a silicone-based antifouling agent, the slipperiness when touched with a finger, a pen, or the like is improved, resulting in a good tactile sensation.

[0095] The content of the antifouling agent is preferably, for example, 0.01 parts by mass or more and 3.0 parts by mass or less relative to 100 parts by mass of the resin component. If the content of the antifouling agent is too small, sufficient antifouling properties may not be imparted to the hard coat layer, and if the content of the antifouling agent is too large, the hardness of the hard coat layer may decrease.

[0096] (v) Other additives The hard coat layer may further contain additives as necessary.The additives are appropriately selected according to the function to be imparted to the hard coat layer, and are not particularly limited, and may include, for example, inorganic or organic particles for adjusting the refractive index, infrared absorbing agents, antiglare agents, antifouling agents, antistatic agents, colorants such as blue dyes and purple dyes, leveling agents, surfactants, lubricants, various sensitizers, flame retardants, adhesion promoters, polymerization inhibitors, antioxidants, light stabilizers, surface modifiers, etc.

[0097] (b) Structure of the hard coat layer The hard coat layer may be a single layer, or may have a multi-layer structure of two or more layers. When the hard coat layer has a multi-layer structure, for example, it is preferable that the hard coat layer has a first hard coat layer provided on the cured film side, and a second hard coat layer provided on the side opposite to the cured film side of the first hard coat layer.

[0098] The first hard coat layer preferably contains the above-mentioned cured product of the polyfunctional (meth)acrylate as a resin component, and also contains silica fine particles dispersed in the resin component. The second hard coat layer preferably contains the above-mentioned cured product of the polyfunctional (meth)acrylate as a resin component. The second hard coat layer may also contain polyfunctional urethane (meth)acrylate and / or polyfunctional epoxy (meth)acrylate as a resin component in addition to the polyfunctional (meth)acrylate. Furthermore, the second hard coat layer may contain the above-mentioned silica fine particles.

[0099] (c) Thickness of the hard coat layer The thickness of the hard coat layer may be appropriately selected depending on the material of the hard coat layer, the function of the hard coat layer, and the use of the laminate. The laminate film in the present disclosure can use the semi-cured transparent film described above. The semi-cured transparent film has less warping, so the hard coat layer can be formed thick. The thickness of the hard coat layer is, for example, 10 μm or more, may be 20 μm or more, or may be 40 μm or more. On the other hand, it may be, for example, 100 μm or less, may be 80 μm or less, or may be 70 μm or less.

[0100] (2-2) Other layers Other examples of the functional layer include an antiglare layer and a primer layer.

[0101] The laminated film of the present disclosure may have an antiglare layer as a functional layer. When the functional layer has an antiglare layer, the laminated film of the present disclosure may have a hard coat layer between the antiglare layer and the cured film. By forming the antiglare layer, it is possible to suppress the reflection of light on the surface of the laminated film of the present invention, and when the laminated film of the present invention is used in an image display device, it is possible to suppress the reflection of external light and suppress glare.

[0102] The antiglare layer may be any layer having antiglare properties, and preferably contains a resin and fine particles. The fine particles form irregularities on the surface of the antiglare layer, thereby exerting the antiglare properties.

[0103] The fine particles are not particularly limited as long as they exhibit anti-glare properties, but are preferably light-transmitting fine particles. In addition, the fine particles may be either inorganic or organic. The shape of the fine particles may be, for example, spherical, elliptical, amorphous, rectangular, cuboid, or the like.

[0104] As the resin, it is preferable to use a curable resin, and for example, a thermosetting resin or an ionizing radiation curable resin that is cured by ionizing radiation such as ultraviolet light or an electron beam can be used. As the curable resin, those generally used for antiglare layers can be used.

[0105] 3. Characteristics of laminated film (a) Pencil hardness When the laminate film of the present disclosure has a hard coat layer as a functional layer, the pencil hardness of the surface on the functional layer side is preferably 8H or more, and more preferably 9H or more.

[0106] Here, the pencil hardness is measured by a pencil hardness test specified in JIS K5600-5-4 (1999). Specifically, a pencil hardness test specified in JIS K5600-5-4 (1999) is performed on the surface of the hard coat layer side of the laminated film using a test pencil specified in JIS-S-6006, and the highest pencil hardness that does not cause scratches is evaluated. The measurement conditions are an angle of 45°, a load of 750 g, a speed of 0.5 mm / sec, and a temperature of 23±2°C. As a pencil hardness tester, for example, a pencil scratch coating hardness tester manufactured by Toyo Seiki Co., Ltd. can be used.

[0107] (b) Ultimate tensile strength The maximum tensile strength of the laminated film in the present disclosure can be, for example, 40N / 20mm or more, and more preferably 50N / 20mm or more. The tensile strength of the laminated film may be 80N / 20mm or less, or 70N / 20mm or less. The maximum tensile strength of the laminated film is measured by using a test piece of 100mm x 20mm, placing the test piece in a tensile tester so that the chuck distance is 60mm, and setting the tensile speed to 10mm / sec. As the tensile tester, for example, Instron 5565 (manufactured by Instron Japan) or Force Tester MCT2150 (manufactured by A&D) can be used.

[0108] (c) Total light transmittance and haze The total light transmittance of the laminated film in the present disclosure is, for example, preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more. Such a high total light transmittance leads to good transparency, and the film can be suitably used for optical applications, particularly display devices.

[0109] The total light transmittance of the laminated film can be measured in accordance with JIS K7361-1:1999, for example, by using a haze meter HM150 manufactured by Murakami Color Research Laboratory.

[0110] The haze of the laminated film in the present disclosure is, for example, preferably 5% or less, more preferably 2% or less, and even more preferably 1% or less. Such a low haze results in good transparency, making it suitable for use in display devices.

[0111] The haze of the laminated film can be measured in accordance with JIS K-7136:2000, for example, by using a haze meter HM150 manufactured by Murakami Color Research Laboratory.

[0112] 4.Applications The laminate film according to the present disclosure is used for optical applications, such as display devices.

[0113] The laminate film of the present disclosure can be used as a member disposed on the viewer side of the display panel, i.e., as a front panel, in such a display device. The laminate film of the present disclosure can be used in display devices used in electronic devices such as smartphones, tablet terminals, wearable terminals, personal computers, televisions, digital signage, public information displays (PIDs), and in-vehicle displays.

[0114] When the laminated film of the present disclosure is disposed on the surface of a display device, it may be disposed so that the cured film side faces the display panel side and the functional layer faces outward, or it may be disposed so that the surface of the functional layer side faces the display panel side and the surface of the cured film side faces outward. When the functional layer is a hard coat layer, the former is preferred.

[0115] D. Manufacturing method of laminated film The present disclosure provides a method for producing a laminated film, comprising: a coating layer B formation step of applying an ultraviolet-curable resin composition B for a functional layer to one side of the above-mentioned transparent film to form a coating layer B, thereby obtaining a laminate having the above-mentioned transparent film and the above-mentioned coating layer B; and an integral curing step of irradiating the above-mentioned laminate with ultraviolet light to cure the transparent film and the coating layer B as a whole, thereby obtaining a cured film from the transparent film and obtaining the above-mentioned functional layer from the coating layer B.

[0116] According to the present disclosure, since the transparent film described above is used, a laminated film having high surface hardness and suppressed brittleness can be produced. In addition, by curing the transparent film and the coating layer B together, curing shrinkage occurs in both the transparent film and the coating layer B, so that a laminated film with suppressed warping can be produced. Furthermore, since the unreacted functional group of the transparent film reacts with the functional group contained in the functional layer, a laminated film with high adhesion strength between the cured film and the functional layer can be obtained.

[0117] 1. Coating layer B formation process This step is a step of forming a coating layer B by applying an ultraviolet-curable resin composition B for a functional layer to one surface of the transparent film described above.

[0118] When the functional layer is a hard coat layer, the ultraviolet curable resin composition described in detail in the above-mentioned material for the hard coat layer can be used as the ultraviolet curable resin composition B. As a method for forming the hard coat layer, for example, a method of applying a curable resin composition for hard coat layer containing the ultraviolet curable compound and the like onto the transparent film and curing the composition can be used.

[0119] The curable resin composition for the hard coat layer contains the above-mentioned ultraviolet-curable compound, and may further contain a polymerization initiator, particles, a solvent, an additive, and the like, as necessary.

[0120] The method for applying the ultraviolet-curable resin composition B onto the transparent film is not particularly limited as long as it is a method that allows application to a desired thickness, and examples of the method include general application methods such as gravure coating, gravure reverse coating, gravure offset coating, spin coating, roll coating, reverse roll coating, blade coating, dip coating, screen printing, etc. In addition, a transfer method can also be used as a method for forming a coating film of the ultraviolet-curable resin composition B.

[0121] The coating film (coating layer B) of the ultraviolet curable resin composition B is dried as necessary to remove the solvent. Examples of the drying method include drying under reduced pressure, drying by heating, and a combination of these drying methods. For example, the coating film can be dried by heating at a temperature of 30° C. or higher and 120° C. or lower for 10 seconds to 180 seconds.

[0122] 2.Integrated curing process In this step, the transparent film and the coating layer B are cured as a unit to obtain a cured film from the transparent film and the functional layer from the coating layer B.

[0123] The amount of ultraviolet light irradiation (accumulated light amount) in this step is, for example, 100 mJ / cm 2 ~1500mJ / cm 2 and preferably in the range of 100 mJ / cm 2 ~800mJ / cm 2 It is more preferable that the range is within the range. It is preferred that this step results in a crosslinking rate of the cured film falling within the above-mentioned range.

[0124] E.Display device The display device according to the present disclosure includes a display panel and the laminate film disposed on the viewer side of the display panel. Since the display device according to the present disclosure includes the laminate film, the display device has excellent scratch resistance and impact resistance.

[0125] Fig. 9 is a schematic cross-sectional view showing an example of a display device according to the present disclosure. As shown in Fig. 9, a display device 50 includes a display panel 51 and a laminate film 10 arranged on the viewer side of the display panel 51. In the display device 50, the laminate film 10 is used as a member arranged on the front surface of the display device 50, and an adhesive layer 52 is arranged between the laminate film 10 and the display panel 51.

[0126] The laminated film in the present disclosure may be the same as the laminated film described above. The laminated film may be arranged so that the transparent film side is the display panel side and the functional layer is the outside, or the surface on the functional layer side is the display panel side and the surface on the transparent film side is the outside. When the functional layer is a hard coat layer, the former is preferred.

[0127] Examples of the display panel in the present disclosure include display panels used in display devices such as liquid crystal display devices, organic EL display devices, and LED display devices.

[0128] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0129] The present disclosure will be described in further detail below with reference to examples and comparative examples.

[0130] Example 1 <Manufacturing transparent films> First, two substrate films having smooth surfaces were prepared (preparation step). A polyester film (A4160 Cosmoshine: manufactured by Toyobo Co., Ltd.) was used as the substrate film. Next, a UV-curable resin composition A1 for transparent films having the following composition was applied to the smooth surface of the non-easy-adhesion surface of one of the substrate films to form a coating layer A (coating layer A formation step). (Ultraviolet curable resin composition A1) Polymerizable polymer 1 represented by the following general formula (3) (Iupizeta RX-0620U, manufactured by Mitsubishi Gas Chemical Company, Inc.): 15 parts by mass

[0131] [ka] (In the formula, R 3 and R 4 are -C(CH3)2CH2OC(=O)CH=CH2, and n1 is about 90. Polyfunctional (meth)acrylate monomer (dipentaerythritol hexaacrylate (DPHA)): 40 parts by mass Cyclopolymerizable monomer (methyl α-allyloxymethylacrylate (AOMA)): 35 parts by weight Bifunctional monomer (tricyclodecane dimethanol diacrylate (product name: Light Acrylate DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.): 10 parts by mass Polymerization initiator (BASF Japan Ltd., product name: Omnirad 184): 5 parts by mass

[0132] Next, the other substrate film was laminated so that the smooth surface was in contact with the coating layer to form a laminate film (lamination process). The laminate film was irradiated with ultraviolet light to semi-cure it, and a transparent film was obtained from the coating layer A (semi-cure process). The ultraviolet light was irradiated at a dose of 100 mJ / cm2 on one side. 2 The sample was irradiated from both sides (200 mJ / cm on both sides). 2 Finally, the two base films were peeled off from the laminate film to obtain a single transparent film (peeling step).

[0133] <Manufacturing of laminated film> The following ultraviolet-curable resin composition B1 for a hard coat layer was applied onto the obtained transparent film, and after drying, the film was irradiated with ultraviolet light from one side at a dose of 20 mJ / cm. 2 The resulting mixture was cured by irradiating it with ultraviolet light at a temperature of 150° C. to form a first hard coat layer (lower layer). During this process, crosslinking of the transparent film also progressed.

[0134] The ultraviolet-curable resin composition B1 was prepared by mixing the components so as to obtain the composition shown below. (Ultraviolet curable resin composition B1) Mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.) 50 parts by weight Solvent (dimethyl glycol) 10 parts by weight Reactive silica particles (average particle size 25 nm, manufactured by JGC Catalysts and Chemicals Co., Ltd.): 40 parts by weight (based on 100% solids) Polymerization initiator (BASF Japan Ltd., product name: Omnirad 184): 4 parts by mass

[0135] Next, the following UV-curable resin composition B2 for the hard coat layer was applied onto the first hard coat layer (lower layer), and after drying, the composition was irradiated with UV light from one side at a dose of 780 mJ / cm 2 . 2 The resulting mixture was cured by irradiating with ultraviolet light at 400° C. to form a second hard coat layer (upper layer). At this time, crosslinking of the transparent film also progressed. In this way, a laminated film was produced. The total thickness of the first hard coat layer and the second hard coat layer was 50 μm. (Ultraviolet curable resin composition B2) Mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.) 70 parts by weight Solvent (dimethyl glycol) 30 parts by weight Antifouling agent (X71-1203M (Shin-Etsu Chemical Co., Ltd.)): 0.25 parts by weight Polymerization initiator (BASF Japan Ltd., product name: Omnirad 184): 4 parts by mass

[0136] Example 2 A transparent film was produced in the same manner as in Example 1, except that the ultraviolet-curable resin composition A2 for a transparent film having the following composition was used instead of the ultraviolet-curable resin composition A1. Furthermore, a laminated film was produced in the same manner as in Example 1 using the produced transparent film. (Ultraviolet curable resin composition A2) 1:5 parts by weight of the polymerizable polymer represented by the above general formula (3) Polyfunctional (meth)acrylate monomer (dipentaerythritol hexaacrylate (DPHA)): 40 parts by mass Cyclopolymerizable monomer (methyl α-allyloxymethylacrylate (AOMA)): 45 parts by mass Bifunctional monomer (tricyclodecane dimethanol diacrylate (product name: Light Acrylate DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.): 10 parts by mass Polymerization initiator (BASF Japan Ltd., product name: Omnirad 184): 5 parts by mass

[0137] Example 3 A transparent film was produced in the same manner as in Example 1, except that a transparent film-forming ultraviolet-curable resin composition A3 having the following composition was used instead of the ultraviolet-curable resin composition A1. Furthermore, a laminated film was produced in the same manner as in Example 1 using the produced transparent film. (UV curable resin composition A3) Polymerizable polymer represented by the above general formula (3): 1: 30 parts by mass Polyfunctional (meth)acrylate monomer (dipentaerythritol hexaacrylate (DPHA)): 40 parts by mass Cyclopolymerizable monomer (methyl α-allyloxymethylacrylate (AOMA)): 30 parts by weight Polymerization initiator (BASF Japan Ltd., product name: Omnirad 184): 5 parts by mass

[0138] Comparative Example 1 A transparent film was produced in the same manner as in Example 1, except that a transparent film-forming ultraviolet-curable resin composition A4 having the following composition was used instead of the ultraviolet-curable resin composition A1. Furthermore, a laminated film was produced in the same manner as in Example 1 using the produced transparent film. (Transparent film forming composition A4) Polyfunctional (meth)acrylate monomer (dipentaerythritol hexaacrylate (DPHA)): 40 parts by mass Cyclopolymerizable monomer (methyl α-allyloxymethylacrylate (AOMA)): 50 parts by weight Bifunctional monomer (tricyclodecane dimethanol diacrylate (product name: Light Acrylate DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.): 10 parts by mass Polymerization initiator (BASF Japan Ltd., product name: Omnirad 184): 5 parts by mass

[0139] Comparative Example 2 A transparent film was produced in the same manner as in Example 1, except that the ultraviolet-curable resin composition A5 for forming a transparent film having the following composition was used instead of the ultraviolet-curable resin composition A1. Furthermore, a laminated film was produced in the same manner as in Example 1 using the produced transparent film. (UV curable resin composition A5) 1:2 parts by mass of the polymerizable polymer represented by the above general formula (3) Polyfunctional (meth)acrylate monomer (dipentaerythritol hexaacrylate (DPHA)): 40 parts by mass Cyclopolymerizable monomer (methyl α-allyloxymethylacrylate (AOMA)): 48 parts by weight Bifunctional monomer (tricyclodecane dimethanol diacrylate (product name: Light Acrylate DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.): 10 parts by mass Polymerization initiator (BASF Japan Ltd., product name: Omnirad 184): 5 parts by mass

[0140] Comparative Example 3 A transparent film was produced in the same manner as in Example 1, except that a transparent film-forming ultraviolet-curable resin composition A6 having the following composition was used instead of the ultraviolet-curable resin composition A1. Furthermore, a laminated film was produced in the same manner as in Example 1 using the produced transparent film. (Ultraviolet curable resin composition A6) Urethane acrylate (Kyoeisha Chemical UA306A): 70 parts by weight Bifunctional monomer (tricyclodecane dimethanol diacrylate (product name: Light Acrylate DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.): 30 parts by mass Polymerization initiator (BASF Japan Ltd., product name: Omnirad 184): 5 parts by mass

[0141] Comparative Example 4 A transparent film was produced in the same manner as in Example 1, except that a transparent film-forming ultraviolet-curable resin composition A7 having the following composition was used instead of the ultraviolet-curable resin composition A1. Furthermore, a laminated film was produced in the same manner as in Example 1 using the produced transparent film. (Ultraviolet curable resin composition A7) Polymerizable polymer represented by the above general formula (3): 1: 40 parts by mass Cyclopolymerizable monomer (methyl α-allyloxymethylacrylate (AOMA)): 60 parts by weight Polymerization initiator (BASF Japan Ltd., product name: Omnirad 184): 5 parts by mass

[0142] (Method of measuring the density of luminance maximum points) The luminance maximum density of the obtained transparent film was measured by the above-mentioned method. The results are shown in Table 1. FIG. 5(a) shows the thickness direction D of the transparent film obtained in Example 1. T FIG. 5(b) is an enlarged view of the rectangular frame in FIG. 5(a), and the brightness maximum point is indicated by M. Similarly, the analysis image and enlarged view of the transparent film obtained in Example 3 are shown in FIG. 6(a) and FIG. 6(b). The analysis image and enlarged view of the transparent film obtained in Comparative Example 1 are shown in FIG. 7(a) and FIG. 7(b). The analysis image and enlarged view of the transparent film obtained in Comparative Example 2 are shown in FIG. 8(a) and FIG. 8(b).

[0143] (crosslinking rate of transparent film) The crosslinking rate of the obtained transparent film was measured by the above-mentioned method. Specifically, the absorption spectrum of the uncured ultraviolet-curable resin composition and the transparent film was obtained by IR measurement (infrared spectroscopy measurement). In Example 1, the peak (810 cm) derived from the (meth)acryloyl group of the transparent film was -1 The peak intensity (absorbance) P1 at 810 cm for the ultraviolet-curable resin composition A1 was 0.072. -1 The peak intensity (absorbance) P0 near this point was 0315. From these results, the crosslinking rate of the transparent film was calculated to be 77% using the following formula. The crosslinking rates of the transparent films of Example 2, Example 3, and Comparative Examples 1 to 3 were determined in the same manner. The results are shown in Table 1. Crosslinking rate (%) = (1 - (peak strength P1 of transparent film / peak strength P0 of uncured ultraviolet-curable resin composition)) x 100 (%)

[0144] (Rating 1: Pencil hardness) The pencil hardness of the surface of the hard coat layer of the obtained laminated film was measured. Specifically, a pencil hardness test specified in JIS K5600-5-4 (1999) was performed on the surface of the hard coat layer of the laminated film using a test pencil specified in JIS-S-6006, and the highest pencil hardness that did not cause scratches was evaluated. The measurement conditions were an angle of 45°, a load of 750 g, a speed of 0.5 mm / sec, and a temperature of 23±2°C. A pencil scratch coating hardness tester manufactured by Toyo Seiki Co., Ltd. was used as the pencil hardness tester.

[0145] (Rating 2: Maximum tensile strength) The maximum tensile strength (N / 20mm) of the obtained laminated film was measured. Specifically, a test piece of 100mm x 20mm was cut out from the obtained laminated film, and the test piece was placed in a tensile tester so that the chuck distance was 60mm, and the maximum tensile strength was measured at a tensile speed of 10mm / min. A Force Tester MCT2150 (manufactured by A&D Co., Ltd.) was used as the tensile tester.

[0146] (Rating 3: Warping) The obtained laminated film (size 50 mm×50 mm) was placed on a horizontal table, and the average value of the warpage (mm) at the four corners of the laminated film was measured and evaluated according to the following evaluation criteria. The results are shown in Table 1. Evaluation criteria A: Less than 10 mm B:10mm or more

[0147] [Table 1]

[0148] As shown in Table 1, the laminated films of Examples 1 to 3 using transparent films having a cross-sectional brightness maximum point density in the thickness direction within a predetermined range showed higher pencil strength and maximum tensile strength than the laminated films of Comparative Examples 1 to 3. In addition, the warping of the laminated films was reduced. In Comparative Example 4, the transparent film could not be produced because it was not completely dissolved in the cyclopolymerizable monomer and could not be made into ink.

[0149] That is, the present disclosure provides the following inventions.

[0150] [1] An optically transparent film, the transparent film contains a semi-cured ultraviolet-curable resin, The density of maximum brightness points calculated from an image of a cross section of the transparent film in the thickness direction observed by a scanning electron microscope is 20 points / μm 2 More than 200 pieces / μm 2 Below is a transparent film.

[0151] [2] The transparent film according to [1], wherein the crosslinking rate of the transparent film is 20% or more and 90% or less.

[0152] [3] The transparent film according to [1] or [2], wherein a pyrolyzate obtained by pyrolyzing the transparent film has a skeleton represented by the following general formula (1):

[0153] [ka] (In the formula, X represents a divalent organic group.)

[0154] [4] The transparent film according to any one of [1] to [3], wherein the transparent film has a thickness of 80 μm or more and 500 μm or less.

[0155] [5] A method for producing a transparent film according to any one of [1] to [4], A preparation step of preparing two substrate films having smooth surfaces; a coating layer A forming step of coating a coating layer A on the smooth surface of one of the base films with an ultraviolet curable resin composition A having a polymerizable polymer having a skeleton represented by the following general formula (2) and a multifunctional (meth)acrylate monomer having three or more (meth)acryloyl groups in the molecule; a lamination step of laminating the other substrate film so that the smooth surface is in contact with the coating layer A to form a laminate film; and a semi-curing step of irradiating the laminate film with ultraviolet light to semi-cure the coating layer A and obtain the transparent film from the coating layer A.

[0156] [ka] (In the formula, X represents a divalent organic group, and R 1 and R 2 each independently represents a (meth)acryloyl group-containing group, and n represents the average degree of polymerization and is a number from 50 to 130.

[0157] [6] The method for producing a transparent film according to [5], wherein in the semi-curing step, the coating layer A is semi-cured so that the cross-linking rate is 20% or more and 90% or less.

[0158] [7] The method for producing a transparent film according to [5] or [6], further comprising a peeling step of peeling the two base films from the laminate film after the semi-curing step to obtain the transparent film alone.

[0159] [8] a cured film containing an ultraviolet curable resin; a functional layer disposed on one surface of the cured film; The density of maximum brightness points calculated from an image of a cross section of the cured film in the thickness direction observed by a scanning electron microscope is 20 points / μm 2 More than 200 pieces / μm 2 The laminated film is as follows.

[0160] [9] The laminated film according to [8], wherein the crosslinking rate of the cured film is 50% or more.

[0161]

[10] The laminate film according to any one of [8] and [9], wherein a pyrolysate obtained by pyrolyzing the cured film has a skeleton represented by the following general formula (1):

[0162] [ka] (In the formula, X represents a divalent organic group.)

[0163]

[11] The transparent film according to any one of [8] to

[10] , wherein the thickness of the cured film is 80 μm or more and 500 μm or less.

[0164]

[12] The laminate film according to any one of [8] to

[11] , wherein the functional layer is a hard coat layer.

[0165]

[13] The laminate film according to

[12] , wherein the laminate film has a maximum tensile strength of 40 N / 20 mm or more.

[0166]

[14] The laminate film according to

[12] or

[13] , wherein the surface of the laminate film on the hard coat layer side has a pencil hardness of 8H or more.

[0167]

[15] The laminate film according to any one of

[12] to

[14] , wherein the hard coat layer contains inorganic particles.

[0168]

[16] The laminate film according to any one of

[12] to

[15] , wherein the hard coat layer contains at least one of a silicone-based antifouling agent and a fluorine-based antifouling agent.

[0169]

[17] A coating layer B forming step of forming a coating layer B by applying an ultraviolet-curable resin composition B for a functional layer to one surface of the transparent film according to any one of [1] to [4] to obtain a laminate having the transparent film and the coating layer B; and an integral curing process in which the laminate is irradiated with ultraviolet light to integrally cure the transparent film and the coating layer B, thereby obtaining a cured film from the transparent film and obtaining the functional layer from the coating layer B.

[0170]

[18] The method for producing a laminated film according to

[17] , wherein the functional layer is a hard coat layer.

[0171]

[19] A display panel; A laminate film according to any one of [8] to

[16] , which is disposed on a viewer side of the display panel; A display device comprising: [Explanation of symbols]

[0172] 1 … Transparent film 2 … Functional layer 10...Laminated film 11... Hardened film 50…Display device 51 ... Display panel

Claims

1. An optically transparent film, the transparent film contains a semi-cured ultraviolet-curable resin, The density of maximum brightness points calculated from an image of a cross section of the transparent film in the thickness direction observed by a scanning electron microscope is 20 points / μm 2 More than 200 pieces / μm 2 Below is a transparent film.

2. The transparent film according to claim 1 , wherein the cross-linking rate of the transparent film is 20% or more and 90% or less.

3. 2. The transparent film according to claim 1, wherein a pyrolyzate obtained by pyrolyzing the transparent film has a skeleton represented by the following general formula (1): 【Chemistry 1】 (In the formula, X represents a divalent organic group.)

4. The transparent film according to claim 1 , wherein the transparent film has a thickness of 80 μm or more and 500 μm or less.

5. A method for producing a transparent film according to claim 1, A preparation step of preparing two substrate films having smooth surfaces; a coating layer A forming step of coating an ultraviolet curable resin composition A having a polymerizable polymer having a skeleton represented by the following general formula (2) and a multifunctional (meth)acrylate monomer having three or more (meth)acryloyl groups in the molecule on the smooth surface of one of the base films to form a coating layer A; a lamination step of laminating the other substrate film such that the smooth surface is in contact with the coating layer A to form a laminate film; and a semi-curing step of irradiating the laminate film with ultraviolet light to semi-cure the coating layer A and obtain the transparent film from the coating layer A. 【Chemistry 2】 (In the formula, X represents a divalent organic group, R 1 and R 2 each independently represents a (meth)acryloyl group-containing group, and n represents the average degree of polymerization and is a number from 50 to 130.

6. The method for producing a transparent film according to claim 5 , wherein in the semi-curing step, the coating layer A is semi-cured so that a cross-linking rate is 20% or more and 90% or less.

7. The method for producing a transparent film according to claim 5 , further comprising a peeling step of peeling the two base films from the laminate film after the semi-curing step to obtain the transparent film alone.

8. a cured film containing an ultraviolet curable resin; a functional layer disposed on one surface of the cured film; The density of maximum brightness points calculated from an image of a cross section of the cured film in the thickness direction observed by a scanning electron microscope is 20 points / μm 2 More than 200 pieces / μm 2 The laminated film is as follows.

9. The laminated film according to claim 8 , wherein the cured film has a crosslinking rate of 50% or more.

10. The laminate film according to claim 8 , wherein a pyrolysate obtained by pyrolyzing the cured film has a skeleton represented by the following general formula (1): 【Chemistry 3】 (In the formula, X represents a divalent organic group.)

11. The laminate film according to claim 8 , wherein the cured film has a thickness of 80 μm or more and 500 μm or less.

12. The laminated film according to claim 8 , wherein the functional layer is a hard coat layer.

13. The laminate film according to claim 12, wherein the laminate film has an ultimate tensile strength of 40 N / 20 mm or more.

14. The laminate film according to claim 12, wherein the surface of the laminate film on the hard coat layer side has a pencil hardness of 8H or more.

15. The laminate film according to claim 12 , wherein the hard coat layer contains inorganic particles.

16. The laminate film according to claim 12 , wherein the hard coat layer contains at least one of a silicone-based antifouling agent and a fluorine-based antifouling agent.

17. A coating layer B forming step of forming a coating layer B by applying an ultraviolet-curable resin composition B for a functional layer to one surface of the transparent film according to claim 1 to obtain a laminate having the transparent film and the coating layer B; and an integral curing process in which the laminate is irradiated with ultraviolet light to cure the transparent film and the coating layer B as a whole, thereby obtaining a cured film from the transparent film and obtaining the functional layer from the coating layer B.

18. The method for producing a laminated film according to claim 17, wherein the functional layer is a hard coat layer.

19. A display panel; A display device according to any one of claims 8 to 16, arranged on the viewer side of the display panel. The laminated film according to claim 1 , A display device comprising:

Citation Information

Patent Citations

  • Surface protection film and method for producing the same

    JP6677537B2

  • Cover film and manufacturing method thereof

    JP6844057B1